2019
DOI: 10.3390/ijerph16132264
|View full text |Cite
|
Sign up to set email alerts
|

Physical Status and Parent-Child Feeding Behaviours in Children and Adolescents with Down Syndrome in The United Arab Emirates

Abstract: The prevalence of Down syndrome (DS) in the United Arab Emirates (UAE) is high in comparison to the global statistics. The aim of this study is to assess the physical status, feeding problems, parent-child feeding relationship and weight outcome in children and adolescents with DS in the UAE. In this cross-sectional study, 83 individuals aged between 2–19 years with DS were recruited from three humanitarian centres for differently abled in the Emirates of Sharjah and Dubai, UAE. Socio-demographic characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
(41 reference statements)
2
15
2
2
Order By: Relevance
“…Reports on parental feeding practice showed that parents had greater weight concern, used more restrictions (36) and less pressure to eat in their feeding practice of their child with DS compared to siblings (38). Similar, among parents of overweight children with DS use of restrictions and monitoring of food intakes was more frequent (39).…”
Section: Parental Feeding Practice and Eating Behavioursmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports on parental feeding practice showed that parents had greater weight concern, used more restrictions (36) and less pressure to eat in their feeding practice of their child with DS compared to siblings (38). Similar, among parents of overweight children with DS use of restrictions and monitoring of food intakes was more frequent (39).…”
Section: Parental Feeding Practice and Eating Behavioursmentioning
confidence: 99%
“…Preference for selected types of foods were reported as a common food related behaviour in children with DS (36). Despite the fact that children with DS have higher rates of feeding problems and often reduced feeding skills, no correlation between parent reported difficult mealtime behaviours and feeding skills was observed (37).…”
Section: Feeding and Swallowing Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of body fat (PBF) measured by bioelectrical impedance is higher in young people with DS [ 48 ]. According to Osaili et al, PBF is elevated in female DS children and adolescents compared to males [ 49 ]. In adults, a study shows no difference in percentage of obesity between male and female DS individuals [ 43 ].…”
Section: Ds and Obesitymentioning
confidence: 99%
“…Due to insufficient mastication associated with rapid swallowing without chewing, DS people can develop a secondary bulimia. In a study of 83 children and adolescents with DS, food selectivity represents 62.2% of feeding difficulties, continued eating in the presence of food 57.7% and swallowing without sufficient chewing 50% [ 49 ].…”
Section: Ds and Obesitymentioning
confidence: 99%